DNA metabarcoding captures subtle differences in forest beetle communities following disturbance. Issue 6 (10th October 2020) - Liu, Mingxin; Baker, Susan C.; Burridge, Christopher P.; Jordan, Gregory J.; Clarke, Laurence J.
Abstract : DNA metabarcoding is an emerging approach for monitoring biodiversity, but uncertainties remain about its capacity to detect subtle differences in invertebrate community composition comparable to those achievable based on conventional morphological identification. In this study, DNA metabarcoding and morphology‐based approaches were compared as tools for investigating whether logging history impacted beetle communities in Tasmanian wet eucalypt forests. We compared 12 unlogged mature forest sites with 12 neighboring regeneration sites that had been logged approximately 55 years previously. The number of species identified based on morphology (173) was close to the number of zero‐radius operational taxonomic units (ZOTUs) identified by DNA metabarcoding of cytochrome c oxidase subunit I (COI, 176) and 16S ribosomal RNA (16S, 156) markers. Subtle but significant differences in beetle species composition between regeneration and unlogged mature forests were captured by both morphology‐based and COI DNA metabarcoding approaches, but not by 16S DNA metabarcoding. Our results support the suitability of mitochondrial COI for studying invertebrate biodiversity. A slight loss of signal compared to the morphology‐based approach may be resolved by developing more comprehensive DNA reference databases. While confirming forest recovery of 48–58 years did not fully restore mature forest beetle communities, we suggest that DNA metabarcoding can be used for monitoring biodiversity and probing subtle differences in community composition.